Effects of Methyl Jasmonate on Flavonoid Accumulation and Physiological Metabolism in Finger Millet (Eleusine coracana L.) Sprouts - Zhangqin Ye; Jing Zhang; Xin Tian; Zhengfei Yang; Jiangyu Zhu; Yongqi Yin (Plants, 2025)
Finger millet (Eleusine coracana L.) is a nutrient-dense cereal with high flavonoid content, yet the mechanisms regulating its secondary metabolite biosynthesis remain underexplored. Various exogenous stimuli can readily activate the enzymatic pathways and gene expression associated with flavonoid biosynthesis in plants, which are regulated by developmental cues. Research has established that methyl jasmonate (MeJA) application enhances secondary metabolite production in plant systems. This investigation examined MeJA’s influence on flavonoid accumulation and physiological responses in finger millet sprouts to elucidate the molecular mechanisms underlying MeJA-mediated flavonoid accumulation. The findings revealed that MeJA treatment significantly suppressed sprout elongation while enhancing the biosynthesis of total flavonoids and phenolic compounds. MeJA treatment triggered oxidative stress responses, with hydrogen peroxide and superoxide anion concentrations increasing 1.84-fold and 1.70-fold compared to control levels at 4 days post-germination. Furthermore, the antioxidant defense mechanisms in finger millet were upregulated following treatment, resulting in significant enhancement of catalase and peroxidase enzymatic activities and corresponding transcript abundance. MeJA application augmented the activities of key phenylpropanoid pathway enzymes—phenylalanine ammonia-lyase (PAL) and cinnamate 4-hydroxylase (C4H)—and upregulated their respective gene expression. At 4 days post-germination, EcPAL and EcC4H transcript levels were elevated 3.67-fold and 2.61-fold, respectively, compared to untreated controls. MeJA treatment significantly induced the expression of downstream structural genes and transcriptional regulators. This study provides a deeper understanding of the mechanism of flavonoid accumulation in foxtail millet induced by MeJA, and lays a foundation for exogenous conditions to promote flavonoid biosynthesis in plants.